PENGARUH KASIH SAYANG ORANG TUA TERHADAP KARAKTER RELIGIUS PESERTA DIDIK KELAS IV MIS AT TAQWA SAMBAS TAHUN PELAJARAN 2019/2020 - Yusfina Aprija; Eliyah; Adnan (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2021)
This journal explains: 1) The love of parents for their children as class IV students of MIS At-Taqwa Sambas for the 2019-2020 Academic Year. 2) The religious character of the fourth grade students of MIS At-Taqwa Sambas for the 2019-2020 academic year. 3) There is the possibility of a significant effect of parental love on the religious character of the fourth grade students of MIS At-Taqwa Sambas for the 2019-2020 academic year. The type and research approach used is a quantitative research type and an associative approach. The population in this study amounted to 44 people. Data collection tools using questionnaires, documentation. The previous questionnaire was tried out and tested for validity and reliability testing. The data analysis technique used Percentage Calculation, Central Tendency and Simple Linear Regression. The results of this study can be concluded as follows: 1. Parents' affection for their children as fourth grade students of MIS At-Taqwa Sambas, is already classified as "very good", namely with a percentage of 90.6%. 2. Karakter religius pada peserta didik kelas IV MIS At-Taqwa Sambas, sudah tergolong “sangat baik” yaitu dengan persentase sebesar 92,5%. There is a significant influence between parental affection on the religious character of fourth grade students Mis At-Taqwa Sambas in the 2019-2020 school year. This can be seen from the relationship between the two variables with a correlation value of 0.411 which lies between 0.400-0.599 which is included in the medium category, with a significant level of 0.016 <0.05, thus (Ha) is accepted and (H0) is rejected. Judging from the results of the calculation that the results a of 50.239 and b obtained 0.467 are found, then the regression equation for parental love and religious character is: Y = 50.239 + 0.467X. From the above equation it means that every one-unit increase in the X variable will be followed by an increase in the Y variable by 0.467 units at a price a = constant. In other words, the magnitude of the influence of variable X on the increase in variable Y is 0.467.